Construction of ion conducting channels by embedding hydrophilic oligomers in piperidine functionalized poly(2, 6-dimethyl-1, 4-phenylene oxide) membranes. (5th January 2021) - Wan, Ruiying; Xu, Shicheng; Wang, Jin; Yang, Yunfei; Zhang, Dengji; He, Ronghuan
Graphical abstract: Highlights: Blending hydrophilic oligomers for improved properties of the polymer membranes. Formation of the ion transport channels with reasonable mechanical and dimensional stabilities. Superior hydroxide conductivity and tolerance to alkali of the blended membranes. The membrane-based single fuel cell shows a peak power density of 328 mW cm −2 . Abstract: A suitable microphase separation morphology has been demonstrated to be an efficient strategy to achieve high ionic conductivity with reasonable durability to anion exchange membranes (AEMs). Herein, hydrophilic oligomers of polyethylene glycols (PEGs) with different molecular weights were blended, separately, with poly(2, 6-dimethyl-1, 4-phenylene oxide) modified by 4, 4-diethoxybutan-1-amine and 1-methylpiperidine (20PDM). The presence of hydrophilic PEGs facilitates the formation of the interconnected nano-channels in the AEMs for ion conduction according to the analysis results by both transmission electron microscopy (TEM) and small angle X-ray scattering (SAXS). The membrane containing 2 wt% PEGs with a molecular weight of 2 kDa reaches a hydroxide conductivity of 97.2 mS cm −1 at 80 °C, which is 25 mS cm −1 higher than that the pristine 20PDM membrane possessing the same ion exchange capacity. A peak power density of 328 mW cm −2 is attained at 60 °C by the proposed membrane based single fuel cell fueling with humidified H2 and O2 with 0.1 MPa of back pressure. The chemical structure, water uptake and swelling as well as resistance to hot alkali solutions of the prepared membranes were investigated.